Among goats and bears: A taphonomic study of the faunal accumulation from Tritons Cave (Lleida, Spain). (April 2020) - Micó, Cristian; Arilla, Maite; Rosell, Jordi; Villalba, Mónica; Santos, Elena; Rivals, Florent; Picin, Andrea; Talamo, Sahra; Blasco, Ruth
Highlights: Tritons Cave unit 2 is analysed for taxonomy, anatomy and taphonomy. The assemblage is characterized by an accumulation of Capra pyrenaica and Ursus arctos. Panthera pardus seems to be the main accumulating agent of the ungulates. Ursids and their altered bones suggest natural deaths and posterior carnivore activity. Abstract: Like human groups, carnivores are able to act on the same faunal accumulation and generate important bone assemblages with their prey remains. In addition, both predators can share the same habitable areas and alternate their occupations, producing the well-known palimpsest at archaeological sites. As a discipline, taphonomy helps us understand the formation of these sites and allows us to identify what occurred before and after the burial of the remains. In order to make an accurate taphonomic interpretation, knowledge of the carnivore ethology is necessary to understand the way that bone accumulations originate and to make inferences about their relationship with human behaviour or other living beings of the environment. In this work, a first taphonomic approach concerning the faunal assemblage of unit 2 of Tritons Cave (Lleida, Catalonia) has been carried out. This unit is characterized by the prevailing presence of the Iberian ibex ( Capra pyrenaica ) and, to a lesser extent, the brown bear ( Ursus arctos ) and cave bear ( Ursus spelaeus ). The survival profile of goats, the alterations observed on the bones, and the consumption patterns seem to indicate that the main agent accumulator is the leopard ( Panthera pardus ); nevertheless, the occasional intrusion and secondary activity of other predators, including hominins, cannot be ruled out. The presence of ursids and the alterations on their bones seem to be related to natural deaths and subsequent carnivore activity, which indicates the high complexity in the assemblage formation. The identification of the leopard as a main taphonomic agent sheds light about these kinds of dens, establishing guidelines to differentiate bone accumulations produced by other carnivores as well as the criteria to identify them within anthropic contexts. Thus, the goal here is to highlight the importance of these types of studies to better understand the relationships and differences between human and carnivore activities in the Iberian Peninsula during the Late Pleistocene age.